Społeczna odpowiedzialność przedsiębiorstwa jako sfera decyzji menedżerskich - Gluszek, Ewa (Corporate Social Responsibility as a Sphere of Managerial Decisions, 2009)
The best form of social involvement are those which make long-term benefits to a company and to the society. They have strategic character, because they let a company consolidate a market position. Such social initiatives include important issues into client value. The option choice determines an organizational model and a form of activity.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 42, s. 139-150